An improved gridded water resource distribution for China based on second-order basin data. Issue 1 (1st January 2019) - Guo, Bing; Yang, Fei; Fan, Yewen; Han, Fang; Jiang, Lin; He, Tianli; Zhang, Hui; Chen, Shuting
Abstract: Water resources are essential for the land surface system and human life and activity. However, gridded water resource data that can reflect subtle differences of spatial distribution within water basins are scarce. This article has introduced six factors: precipitation, aridity, evapotranspiration, slope, vegetation, and catchment area, to develop an improved gridded model for water resource distribution in China based on the partition-weight assignment method. The results showed that the improved gridded water resource distribution method based on second-order basins has high applicability for China. It demonstrates an overall spatialization error of 7.68% for third-order basins and 7.25% for provincial administrative units. In addition, the spatialization precision of the Yangtze River Basin, Songhua River basin, and Southern River Basin, is better than that of the middle and lower reaches of Yellow River Basin, Huaihe River Basin, and Northwestern River Basin. The relationship between the water resource distribution and gross domestic product density differed with the size of urban areas and geographical locations. These results can provide scientific support and databases for the management of regional water resources.